1968
DOI: 10.1161/01.cir.38.5.859
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cerebral Atherosclerosis in Males and Females

Abstract: An evaluation of the influence of sex upon cerebral atherosclerosis was carried out in 5,033 consecutive autopsies studied by a special well-standardized coding technique. A sex difference in frequency of cerebral atherosclerosis appears from the fourth to the sixth decade. During this period the percentage of female cases with no atherosclerosis lags behind the percentage of male cases by a 15-year period. After the sixth decade, the frequency of cerebral atherosclerosis increases more rapidly in females, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 29 publications
2
33
1
2
Order By: Relevance
“…Both of them related with sleep disorders [25,26] and stressful impulses on the hypothalamic nuclei [5,[27][28][29][30][31][32]. Figure 1 represents the hippocampus, which is located in the medial temporal lobes and is constituted by dentate gyrus and the cornu Ammon with their CA1 to CA4 subdivisions [2,13,33,34]. The hippocampus receives descending afferents from the anterior nuclear complex of the thalamus, entorhinal cortex (area 28) and the amygdala (through alveus) [29,31], and ascending afferents from the supramammillary nuclei of the hypothalamus, the septum (origin of cholinergic axons), raphe nuclei (origin of serotoninergic axons) and locus coeruleus (origin of noradrenergic axons) [22,31,35].…”
Section: Hypothalamus and Its Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of them related with sleep disorders [25,26] and stressful impulses on the hypothalamic nuclei [5,[27][28][29][30][31][32]. Figure 1 represents the hippocampus, which is located in the medial temporal lobes and is constituted by dentate gyrus and the cornu Ammon with their CA1 to CA4 subdivisions [2,13,33,34]. The hippocampus receives descending afferents from the anterior nuclear complex of the thalamus, entorhinal cortex (area 28) and the amygdala (through alveus) [29,31], and ascending afferents from the supramammillary nuclei of the hypothalamus, the septum (origin of cholinergic axons), raphe nuclei (origin of serotoninergic axons) and locus coeruleus (origin of noradrenergic axons) [22,31,35].…”
Section: Hypothalamus and Its Dysfunctionmentioning
confidence: 99%
“…Between 25 and 30 years of age, the cerebral blood flow declines progressivelly to mean value of adults (50 -55 mL/100 g/min) [3,33,38]. Deterioration circulatory coincides with the appearance of atherosclerotic plaques in the supraclinoid carotids [34][35][36]39]. Moreover, these plaques located at the mouths of the superior hypophyseal, infundibular and some perforating arteries are responsible for progressive ischemia in the hypothalamus [3,5,40,41].…”
Section: Hypothalamus and Its Dysfunctionmentioning
confidence: 99%
“…From the fourth to sixth decades of life, the percentage of women with no cerebral atherosclerosis was higher than men, but at >65 years of age the frequency of atherosclerotic lesions was the same in 2 sexes. 10 Above all, geographic variation and sex difference in the distribution of ICAS have not been fully discussed before. So, we performed this study with the aim to investigate geographic and sex difference in the distribution of ICAS in China.…”
mentioning
confidence: 99%
“…The location of atherosclerosis depends on many predisposing factors, and the cause of this dependence still remains the subject of research 24) . It is possible that atherosclerosis exhibits selective responses in different vascular beds [25][26][27] . Our data confirmed that atherosclerosis of the ascending aorta seems to be more specific for FH patients even when compared to hypercholesterolemic patients without FH gene mutation.…”
Section: Discussionmentioning
confidence: 99%